Treatment of Unstable Injury of Pelvic Bones in Pregnant (Case Report) - Holovakha, M.L.; Bohdan, O.V.; Kozhemiaka, M.O.; Pertsov, V.I. (TERRA ORTHOPAEDICA, 2021)
Summary. There is no doubt in the relevance of the problem of treatment of patients with unstable fractures of pelvic bones, since these injuries involve a threat to the patient’s life in the early period and often lead to disability in the future. This article presents a rare case of treatment of a patient with an unstable pelvis injury, while being 16 weeks pregnant. Patient A., born 1993, was admitted after a road accident injury. The examinations included: X-ray, CT, ultrasound, and gynecologist consultation. The patient was diagnosed with closed bilateral fracture of the pubic and ischial bones with displacement; rupture of the left sacroiliac joint with the boundary fracture of the sacrum (61-С1.3 by the Tile-AO-ASIF classification). The patient was 16 weeks pregnant. The surgery – open reduction and extramedullary metalosteosynthesis – was performed at the 9th day after the injury. The patient was discharged to outpatient treatment at the 12th day after the surgery. She started walking on crutches 3 weeks after the surgery; no additional support was needed since 1.5 months after the surgery. The patient gave birth at 39 weeks by surgical intervention (caesarean section). The baby’s condition was assessed as 8 according to the Apgar scale. At the control examination 10 months after the surgery, musculoskeletal function of the patient was fully restored.